2014
DOI: 10.1177/0095399714555750
|View full text |Cite
|
Sign up to set email alerts
|

The Increased Importance of Sector Switching: A Study of Trends Over a 27-Year Period

Abstract: Sector switching is new to the public administration literature, and our knowledge about its prevalence and trends is limited. Yet sector switching is an important phenomenon that casts light on public-private differences. We study sector switching in a modern economy, using unique Danish register-based employer-employee data covering more than 25 years. We find that sector switching constitutes 18.5 percent of all job-to-job mobility, and the trend is increasing both from public to private and from private to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Conversely, we found private sector experience to be positively related to turnover. This is not surprising as the public sector companies exhibit strong public sector elements, and job changes have been shown to be more frequent among employees in the private sector (Frederiksen and Hansen ).…”
Section: Resultsmentioning
confidence: 96%
“…Conversely, we found private sector experience to be positively related to turnover. This is not surprising as the public sector companies exhibit strong public sector elements, and job changes have been shown to be more frequent among employees in the private sector (Frederiksen and Hansen ).…”
Section: Resultsmentioning
confidence: 96%
“…This model is characterized by flexible rules for hiring and firing supplemented by a generous social security system (Andersen and Svarer 2007). It should be noted that despite flexible rules for hiring and firing, a recent study found that sector switching among workers is relatively modest in Denmark (Frederiksen and Hansen 2017). In 2014, more than 34 per cent of Danish labour market participants were employed in the public sector.…”
Section: The Danish Employment Contextmentioning
confidence: 99%
“…Adding to this are the so-called sector switchers or those who start in public sector work but eventually leave. In Denmark, for example, researchers have reported a 90% increase in public to private sector moves from 1980 to 2006 (Frederiksen and Hansen 2014). At the global level, research from the USA has shown that federal government employees are more likely to leave government due to economic turbulence (Piatak 2017).…”
Section: How Are They Recruited?mentioning
confidence: 99%